An interpretation of the behavior of the mark up in the Brazilian industry - Aparecida Feijó, Carmem; Cerqueira, Luiz Fernando (Investigación Económica, 2011)
The Brazilian economy experienced significant changes during the 1990s. Economic and financial deregulation, price stabilization and privatizations configured a new economic scenario, shaping new attitudes and strategies of agents. In spite of these changes, economic performance was poor during the decade. Economic growth was marked by short periods of growth followed by deceleration periods. The gross capital formation (or investment) rate, a key variable to explain the dynamism of the economy, was around 17.0%, whereas current estimates by governmental officials point to an investment level of around 25.0% as a requirement for a 5.0% sustained annual growth rate.